Kultusz, pletyka, emlékezet: A kultúra közvetítésének aspektusai Nyáry Krisztián íróportréiban - Baranyai, Norbert (Studia Litteraria, 2018)
The paper analyzes Krisztián Nyáry’s popular Facebook posts and volumes (This is the way they loved, Part One; Part Two) depicting the love life of Hungarian writers and poets. I explore how the short texts dealing with the love adventures of authors are defined by memory, which, in turn, is formed by cultic interpretation (with special focus on the Facebook posts). On the other hand, the popularity of posts is interpreted by describing the function of gossip and by Jan Asssman’s theory of communicative and cultural memory. The two formats of publishing the texts is compared, though only tangentially, with the aim of discovering the way the reception of texts change in relation to the different medial contexts.